PENGARUH GAIRAH DALAM BEKERJA TERHADAP PENYESUAIAN PSIKOLOGIS MENGHADAPI PENSIUN DENGAN KEBUTUHAN KEPUASAN SEBAGAI VARIABEL PEMEDIASI PADA PNS YANG BEKERJA DI KANTOR DINAS WILAYAH KOTA BANDA ACEH - Nurchalis Abdi, Amri (Departemen Manajemen, 2018)
Abstract: This study aims to measure the influence of Passion for Work on Psychological Adjustment to Retirement which is mediated by Satisfaction Needs for Civil Servants Working in the Banda Aceh City Regional Office. The sample used in this study is the Civil Service Officers Office, totaling 105 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used was purposive sampling. Hierarchical Linear Modeling (HLM) is used as an analytical method to determine the effect of all variables involved.Based on the results of HLM analysis, indicates that the Passion for Work affects the Psychological Adjustment to Retirement, Passion for Work influences the Satisfaction Needs,Satisfaction Needs affect the Psychological Adjustment to Retirement and Needss Satisfaction mediate the influence of Passion For Work towards Psychological Adjustment to Retirement.Keywords: Passion for Work, Psychological Adjustment to Retirement, Satisfaction Needs, Hierarchical Linear Modeling